Morphological Description of Noun Formation Process: Case of Suffixation and Prefixation in Iguta Language - Mohammed Ahmad Ado; Siti Jamila Bidin (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2017)
This paper dwells on a concise morphological description of Noun formation process involved in Iguta language (a minority endangered language in the north central, Nigeria). To this end, the paper explores the suffixation and prefixation processes involved in the formation of nouns of Iguta language. Ado’s (2017) 455 Iguta wordlists was employed as secondary data and was qualitatively used as instrument for the analyses in this paper. Ado’s 455 Iguta wordlists is primarily based on the standard dialect (i.e., Andirgiza) spoken by its native speakers in five selected towns in Jos North local government of the Plateau state, Nigeria. Hand analysis strategy and a thematic analytical process were used in developing insights on the language data during the analysis. The findings revealed ‘-char, -di and –e’ morphs as suffixes to inflect while ‘t-, ti-, ha-, a-, an-, m-, i-, ma-, si-, ndu-, s-, tu-, tun-, tumu- morphs as prefixes to either inflect or derive nouns. It is also observed that most singular nouns in Iguta are inflected to produce the plural forms using ti- or tu- prefixes especially when the pattern of the singular words begin with a vowel morpheme or phoneme. In accordance with the findings, it is suggested that prefixes and suffixes are part of the affixation process used in noun formation of Iguta language. In conclusion, the study has contributed in descriptive linguistics in terms inflectional or derivational suffixation and prefixation process used to build nouns in Iguta language. This paper may assist professional teachers and linguists in understanding the suffixations and prefixations existing in Iguta language.